The Effectiveness of the Family-Centered Care (FCC) Educational Model as a Clinical Learning Strategy for the Prevention of Anemia and Stunting - Darmawati Darmawati; Mira Rizkia; Sufriani Sufriani; Mariatul Kiftia; Elka Halifah; Zulkarnaini Zulkarnaini (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: Anemia in pregnancy and stunting in children are interrelated public health problems. This study aimed to evaluate the effectiveness of the Family Centered Care (FCC) educational model as a clinical learning strategy to prevent anemia and stunting.Method: An experimental study with a randomized control design was conducted among 93 third-trimester pregnant women selected through total sampling. Participants were randomly assigned to the intervention group (n = 46) and the control group (n = 47). The intervention group received FCC-based education emphasizing family participation, collaboration, information sharing, and respect, while the control group received standard care. Data were collected before and after the intervention using validated questionnaires, anthropometric measurements, and hemoglobin tests. Data were analyzed using Wilcoxon, Mann–Whitney U, and Independent t-tests with a significance level of p < 0.05.Results: The intervention significantly improved knowledge about anemia (mean difference = +5.50, p < 0.001) and stunting (+2.46, p < 0.001). Hemoglobin levels increased from 10.97 ± 1.23 g/dL to 12.30 ± 1.19 g/dL (p < 0.001), while the control group showed a decline. Height-for-age Z-scores (HAZ) improved within the intervention group (p = 0.002), though between-group differences were not significant (p = 0.909).Conclusion: The Family Centered Care educational model effectively enhanced maternal knowledge and hemoglobin levels, contributing to anemia prevention. It shows potential for improving child growth outcomes.